Guinea : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The health of the population in Guinea is also one of the determinants of poverty, owing to its impact on the ability of the population to work with vigor. There are large disparities depending on the urban/rural residence and administrative region. In terms of the poverty level of households, consultation rates among households in the first and second quintiles (the poorest 40 percent) are considerably lower (67.7 percent and 74.3 percent, respectively) than the national average. Health sector financing remains weak.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet